Application of the infrared thermography method in diagnosis of Raynaud`s phenomenon - Zabolotnyi, D.I.; Loboda, T.V.; Dunaievskyi, V.I.; Kotovskyi , V.Y.; Timofeiev , V.I.; Nazarchuk , S.S. (Medicni Perspektivi, 2023)
The development of modern diagnostic medicine, the important task of which is the use of non-invasive methods for detecting a disease without impact of radiation exposure, has led to the spread of the method of infrared thermography, which allows to quickly and informatively identify pathological conditions of a person within a single examination. The main complaints characteristic of Raynaud's phenomenon are associated with cold, hyperemia, edema, and a feeling of paresthesia in the limbs. A significant number of scientific works have been devoted to the study of the Raynaud's phenomenon, where basically, examples of manifestations of Raynaud's phenomenon are given in the form of a violation of the microcirculation of the distal parts of limbs. Comprehensive studies of the combination of Raynaud's phenomenon with concomitant diseases, according to the authors, are insufficiently covered. The application of sophisticated modern laboratory diagnostic methods to detect this disease is nonspecific and burdensome for the patient. Thermographic diagnostics within one examination reveals both the presence of signs of Raynaud's phenomenon and concomitant somatic diseases. This paper presents the results of many years’ thermographic research, demonstrating the variety of manifestations of the Raynaud's phenomenon. For the first time, it has been shown that patients with signs of Raynaud's phenomenon, as a rule, have concomitant somatic diseases, which should be the subject of research of specialists in different medical fields to determine the relationship of Raynaud's phenomenon with the identified diseases. The results of visualization of thermoasymmetries of the skin of various pathological conditions during a complex thermographic examination were obtained, which greatly simplify the diagnostic search and understanding the complexity and danger of Raynaud's phenomenon. Of particular importance are the results of work for the differential diagnosis of complications of diabetes mellitus – diabetic foot syndrome. The paper presents some results of thermographic examinations of patients with signs of Raynaud's phenomenon and identified pathological changes in the body.